Associations of elevated glucose levels at each time point during OGTT with fetal congenital heart diseases: a cohort study of 72,236 births - Qian Zhang; Shuhua Lai; Yulong Zhang; Xu Ye; Yi Wu; Tinghua Lin; Huiyun Huang; Wenhui Zhang; Hai Lin; Jianying Yan (BMC, 2023)
Abstract Background It remains unclear how the condition of glucose metabolism during pregnancy affects fetal outcomes. This study aimed to investigate the associations of gestational diabetes mellitus (GDM) and elevated glucose levels at each time point during oral glucose tolerance test (OGTT) with congenital heart disease (CHD) risk in offspring. Methods We conducted a retrospective cohort study of mothers with singleton pregnancies of 20 weeks or more registered at Maternal and Child Health Centers in Fujian Province, China. The OGTT results and offspring CHD occurrence were collected. We used logistic regression to analyse the association between elevated blood glucose at each time point during OGTT and CHD. Results A total of 71,703 normal and 533 CHD fetuses were included. Compared to the corresponding normal group, women with GDM, elevated blood glucose at different time points in OGTT (0 h ≥ 5.1 mmol/L, 1 h ≥ 10 mmol/L, and 2 h ≥ 8.5 mmol/L) showed an increased risk of CHD in offspring (adjusted OR = 1.41, 1.36, 1.37, and 1.41, all P < 0.05, respectively). Compared to group 1 (normal OGTT 0 h, 1 h and 2 h), the risk of CHD was higher in group 3 (normal OGTT 0 h and abnormal OGTT 1 h or 2 h) and group 4 (abnormal OGTT 0 h, 1 h and 2 h), OR = 1.53 and 2.21, all P < 0.05, respectively. Moreover, we divided participants by advanced maternal age, multipara, assisted reproduction, fetal sex, and others, similar associations were observed in the subgroup analyses. Conclusion Elevated blood glucose at different time points during OGTT was associated with CHD in offspring. Fetuses of pregnant women with GDM should be screened for a high risk of CHD.